FAKTOR-FAKTOR YANG MEMENGARUHI PEMBERIAN OPINI AUDIT GOING CONCERN - Bayudi, Nanang; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi, 2017)
Going concern audit opinion issued an audit opinion by the auditor to determine whether the company can maintain its viability. Going concern is one of the most important concepts underlying financial reporting and auditor's responsibility to determine the viability of the financial statements. The purpose of this study was to determine the influence of the factors that affect the provision of going concern audit opinion with a number of observations as much as 130 sample obtained by purposive sampling method. Data analysis technique used is the logistic regression analysis. Based on the results of analysis show that variables significantly affect profitability going concern audit opinion. Liquidity variable does not affect the going concern audit opinion. Variable size of the company does not affect the going concern audit opinion. Variable firm size does not affect the going concern audit opinion.
Keywords: Profitability, Liquidity, Company Size, Firm Size, Audit Going Concern